Finger Painting to Improve Fine Motor Skills Children Aged 4-5 Years - Hanna, Tsania Qurrotaainin; Zulkarnaen, Z (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study aims to analyze the process and results of improving children's fine motor skills through finger painting activities at Sahabat Early Childhood Education Center, Colomadu, Karanganyar. This research was conducted due to the need for better stimulation of fine motor skills, as previous methods were less interesting and lacked variety. The method used was qualitative with a collaborative approach, which included observation, interviews, and collective documentation. This study involved six children aged 4–5 years and two educators. The criteria for measuring fine motor skills included three aspects, namely (1) pattern formation, (2) shape conformity, and (3) finger flexibility. The results showed that finger painting activities were very effective in improving children's fine motor skills. Of the six children involved, four (67%) fell into the "Developing as Expected" (DAE) category in all three aspects measured. This improvement was supported by the finger painting activity mechanism, which provided sensory stimulation, strengthened the small muscles in the hands, and improved eye-hand coordination, in accordance with Piaget and Vygotsky's theories, particularly the concept of scaffolding. Additionally, this activity is also very helpful in building children's curiosity, focus, independence, and self-confidence, while replacing less interesting and boring methods. Research indicates that finger painting is a good and enjoyable approach to learning, capable of providing full stimulation for fine motor skills.